THE IMPLEMENTATION OF SCHOOL FINANCIAL MANAGEMENT TO IMPROVE QUALITY OF EDUCATION - Alif, Khairunnisa Putri; Ahmad, Masduki (STKIP Pesisir Selatan, 2023)
This article aims to examine the implementation of school financial management in order to improve the quality of education. The research method used in this article is literature study, in which data is obtained by means of a qualitative ethnographic approach, namely collecting data by making data instruments from interviews, observations, and documentation by respondents, namely principals and teachers. The results of the literature study explain that the implementation of school financial management to improve the quality of education must have the principles of fairness, efficiency, transparency and accountability. Educational financial management that meets at least four financial principles, namely transparency, accountability, effectiveness and efficiency is a benchmark for success in managing funds to achieve educational institution goals. In improving the quality of education in managing financial management in schools, one of the most important factors to achieve this with proper financial planning set forth in the RAPBS, clear sources of fund management, and school financial accountability, evaluation of programs that have been implemented so that school financial management can run effectively and efficiently.